Un partido de futbol - Maccarone, Grace; Johnson, Meredith (New York : Scholastic, 1998)
Brief rhyming text follows a group of children through some exciting plays during a soccer game.
"Cartwheel Books."
"Mariposa, Scholastic en espanol"--P. [4] of cover.
Accelerated Reader
Keywords: Soccer stories; Stories in rhyme -- Juvenile literature